Determination of IgE antibodies to the benzylpenicilloyl determinant: A comparison of the sensitivity and specificity of three radio allergo sorbent test methods - Garcia, Juan J. (J Clin Lab Anal, 1998)
The quantitation of in vitro IgE antibodies to the benzylpenicilloyl determinant (BPO) is a useful tool for evaluating suspected penicillin allergic subjects. Although many different methods have been employed, few studies have compared their diagnostic specificity and sensitivity. In this study, the sensitivity and specificity of three different radio allergo sorbent test (RAST) methods for quantitating specific IgE antibodies to the BPO determinant were compared. Thirty positive control sera (serum samples from penicillin allergic subjects with a positive clinical history and a positive penicillin skin test) and 30 negative control sera (sera from subjects with no history of penicillin allergy and negative skin tests) were tested for BPO‐specific IgE antibodies by RAST using three different conjugates coupled to the solid phase: benzylpenicillin conjugated to polylysine (BPO‐PLL), benzylpenicillin conjugated to human serum albumin (BPO‐HSA), and benzylpenicillin conjugated to an aminospacer (BPO‐SP). Receiver operator control curves (ROC analysis) were carried out by determining different cut‐off points between positive and negative values. Contingence tables were constructed and sensitivity, specificity, negative predictive values (PV–), and positive predictive values (PV+) were calculated. Pearson correlation coefficients (r) and intraclass correlation coefficients (ICC) were determined and the differences between methods were compared by χ(2) analysis. Analysis of the areas defined by the ROC curves showed statistical differences among the three methods. When cut‐off points for optimal sensitivity and specificity were chosen, the BPO‐HSA assay was less sensitive and less specific and had a lower PV– and PV+ than the BPO‐PLL and BPO‐SP assays. Assessment of r and ICC indicated that the correlation was very high, but the concordance between the PLL and SP methods was higher than between the PLL and HSA or SP and HSA methods. We conclude that for quantitating IgE antibodies by RAST to the BPO determinant, BPO‐SP or BPO‐PLL conjugates offer advantages in sensitivity and specificity compared with BPO‐HSA. These results support and extend previous in vitro studies by our group and highlight the importance of the carrier for RAST assays. J. Clin. Lab. Anal. 11:251–257, 1997. © 1997 Wiley‐Liss, Inc.